Las artes escénicas como aporte a la adaptación de estudiantes en situación de movilidad humana, en la Unidad Educativa Nicanor Larrea periodo 2021-2022 - Lorena Abigail, Punguil Fiallos (2022)
ABSTRACT This research project to obtain the title of Master of Education, mention educational inclusion and attention to diversity, titled the performing arts as contribution to the adaptation of students in a situation of human mobility, in the Unit Educativa Nicanor Larrea period 2021-2022, was an investigation with a mixed approach given that qualitative aspects were analyzed in relation to adaptation and quantitative aspects since the number of students in a situation of mobility was identified, in addition to the variables that allowed to validate the proposal through a test pre and post application of the proposal, it was also descriptive, explanatory, of longitudinal design, since data were collecteddata before and after the application of the proposal, of quasi-experimental design sinc performing arts were applied as a proposal and it was identified if there is a significant differenc in the adaptation of students in a situation of human mobility. Among the results obtained in relation to students in a situation of human mobility, it was observed that most do not know if their family moved of their own free will and if they plan to settle permanently in this city, it is also observed that there is in most of the Mobility students have difficulty relating to their peers.classmates. Within the proposal, the most effective didactic strategy was identified.adequate to promote the educational inclusion of students in a situation of mobility human, which was the application of performing arts, specifically the theater, whose purposwas not purely the work as a final product, but promotion of the adaptation through a priori activities through the application of various dynamics focused on the acceptance and adaptation. Through the validation of the proposal it was evidenced that the arts scenic if they contributed to the adaptation of students in a situation of human mobility, at the Nicanor Larrea Educational Unit for the 2021-2022 period. Lastly, the respective conclusions and recommendations based on the research objectives. Keywords: <essence arts>, <theater>, <human mobility>, <acceptance